Optimizing outpatient claim management: The role of sep and document completeness – a qualitative - Ramdhani, Budi; Habibi, Musta'inul (Institute of Computer Science (IOCS), 2025)
Efficient outpatient claim management is essential for hospital financial sustainability, particularly under Indonesia’s National Health Insurance (Jaminan Kesehatan Nasional, JKN) system. This study aimed to explore the challenges and optimization strategies in outpatient claim management at UOBK RSUD R Syamsudin SH, focusing on the role of Participant Eligibility Letter (Surat Eligibilitas Peserta, SEP) and document completeness. A qualitative descriptive approach was applied, using thematic analysis to identify key themes from observations, in-depth interviews, and document analysis. Findings revealed that incomplete claim documents, errors in SEP completion, manual verification bottlenecks, and lack of administrative training significantly contributed to claim delays and rejections. The study suggests that standardized document verification, digital integration with BPJS Kesehatan, and regular staff training are critical for optimizing claim processing. These strategies can improve hospital cash flow, reduce claim rejection rates, and enhance service efficiency. This research provides practical recommendations for hospital administrators and policymakers to refine BPJS claim management, ensuring timely reimbursement and sustainable healthcare financing.